Routing protocols for internet of things: a survey - Romario Bhattacharyya, Tamoghno; M. Pushpalatha, Dr (International Journal of Engineering and Technology, 2018)
The world of wireless sensor network(WSN) is widening day by day and the latest technology in use the Internet of Things known as IOT is the latest craze in it. But the IOT technique and its devices requires routing protocols in situations like low power and lossy networks(LLNs) which brings great challenges. In many and some emergency cases, like in case of large and more data traffic which causes to lead in network congestions and also brings loss in packets and delay. In order to overcome all this problems , many group research and individuals are trying and focusing on different solutions to maximize the throughput for the RPL network. In this paper we will we studying and reviewing some of the different methods that has been taken to maximize the throughput in the network and hence try to come to a conclusion for the future techniques needed to be done.Â Â